2017
DOI: 10.1021/acs.est.6b05775
|View full text |Cite
|
Sign up to set email alerts
|

Metro Commuter Exposures to Particulate Air Pollution and PM2.5-Associated Elements in Three Canadian Cities: The Urban Transportation Exposure Study

Abstract: System-representative commuter air pollution exposure data were collected for the metro systems of Toronto, Montreal, and Vancouver, Canada. Pollutants measured included PM (PM = particulate matter), PM, ultrafine particles, black carbon, and the elemental composition of PM. Sampling over three weeks was conducted in summer and winter for each city and covered each system on a daily basis. Mixed-effect linear regression models were used to identify system features related to particulate exposures. Ambient leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(37 citation statements)
references
References 35 publications
1
35
1
Order By: Relevance
“…The UTES was designed to assess TRAP exposures in Canadian subway [18], private vehicle [19], and bus commuting environments. The predominant use of diesel propulsion in buses may result in higher exposure to diesel exhaust in buses, relative to private vehicles and subways.…”
Section: Comparison With Utes Private Vehicle and Subway Concentrationsmentioning
confidence: 99%
See 2 more Smart Citations
“…The UTES was designed to assess TRAP exposures in Canadian subway [18], private vehicle [19], and bus commuting environments. The predominant use of diesel propulsion in buses may result in higher exposure to diesel exhaust in buses, relative to private vehicles and subways.…”
Section: Comparison With Utes Private Vehicle and Subway Concentrationsmentioning
confidence: 99%
“…Personal exposures to TRAP in commuting environments is a research priority. While commuting represents 5% of a Canadian's day [15], this microenvironment can represent a larger proportion of daily exposure to trafficrelated air pollutants [16][17][18]. The characterization of air pollution in urban transport environments can help refine air pollution exposure estimates as well as inform air quality policy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies evaluating the composition of underground PM compared to PM found in overground light rail and road journeys suggest that, while underground PM may have relatively low concentrations of the carcinogenic polyaromatic hydrocarbons associated with diesel combustion, this may be outweighed by the presence of metals in underground PM, and the sheer airborne concentration of underground PM [14,92]. Indeed, even a relatively short commute in an underground railway may contribute a large proportion of an individual's daily exposure to PM and airborne metals [16]. Therefore, it is perhaps surprising that studies of the effects of acute and chronic exposure to underground railway air have found little evidence of excess risk [93].…”
Section: Inflammatory and Barrier Responses To Pm In Vitromentioning
confidence: 99%
“…Studies carried out in Canada and Barcelona showed that, elemental concentration differs with respect to mode of transport and time of exposure i.e. travel time on which the commuters use the roads [3,36].…”
Section: Elemental Analysis Of Pm 25mentioning
confidence: 99%